PENGARUH STRATEGI COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY TERHADAP HSIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 1 PALU - Haris, Abd. (Katalogis, 2015)
This Research aim to analyse influence of strategy of Cooperative type Learning of two stray two stay to result learn student at history subject in SMA Negeri 1 Palu. Research of this experiment use Randomized Pre Test-Posttest Control Design. Subjek or population in this research is class student of XI IPA SMA Negeri 1 Palu. Sampel Research specified by class of XI IPA 3 as experiment class and class of XI IPA 4 as control class. Technique taker of first phase sampel use purpossive sampling and both/ second phase using sampling random. Independent variable in this research is model of two stay two stray and variable of dependen is score result of learning student history subject of SMA Negeri 1Palu. Data collecting done/conducted with tes result of learning. Instrument Validasi namely and validity of realibilitas instrument counted/calculated to use aid of microsof excel. Test conditions cover test of normalitas use Kolmogorov-Smirnov and homogeneity test use Levene Test. Examination of hypothesis use t test at level of signifikansi 0,05. Result of hypothesis test obtain;get value of p= 0,00 < 0,05 meaning result learn student at experiment class by using model of two stay two stray of result learn student at class control by using conventional study. Thereby can be concluded by model of two stay two stray have.